Studying poetry - Spurr, Barry (South Melbourne : Macmillan Education Australia, 1997)
Reading poetry: Reading aloud, Describing a poem, Varieties of poetic style, Evaluation of poetry. Poetry through the centuries: the Renaissance, the early seventeenth century, the restoration and augustanism, romanticism...
Keywords: Poetry; English poetry; English poetry -- History and criticism; English poetry -- Study and teaching